Long-term U.S transportation electricity use considering the effect of autonomous-vehicles: Estimates & policy observations. (November 2018) - Fox-Penner, Peter; Gorman, Will; Hatch, Jennifer
Abstract: In this paper, we model three layers of transportation disruption – first electrification, then autonomy, and finally sharing and pooling – in order to project transportation electricity demand and greenhouse gas emissions in the United States to 2050. Using an expanded kaya identity framework, we model vehicle stock, energy intensity, and vehicle miles traveled, progressively considering the effects of each of these three disruptions. We find that electricity use from light duty vehicle transport will likely be in the 570–1140 TWh range, 13–26%, respectively, of total electricity demand in 2050. Depending on the pace at which the electric sector decarbonizes, this increase in electric demand could correspond to a decrease in LDV greenhouse gas emissions of up to 80%. In the near term, rapid and complete transport electrification with a carbon-free grid should remain the cornerstones of transport decarbonization policy. However, long-term policy should also aim to mitigate autonomous vehicles' potential to increase driving mileage, urban and suburban sprawl, and traffic congestion while incentivizing potential energy efficiency improvements through both better system management and the lightweighting of an accident-free vehicle fleet. Highlights: U.S. electricity use from light duty vehicles will likely be from 570 to 1140 TWh. U.S. electric sector capacity growth will be able to accommodate electric vehicles. Transport electrification should remain a cornerstone of decarbonization policy. Autonomous vehicles could exacerbate GHG emissions without appropriate policy.